Thin film growth and surface modification by keV ion beam - Choi, SC; Park, YW; Choi, WK; Kim, KH; Cho, JS; Han, S; Cho, J; Jung, S; Han, YG; Yoo, BK; Jung, HJ; Koh, SK (JAPAN J APPLIED PHYSICS, 1998)
High-quality ZnO film and highly wettable polymethylmethacrylate (PMMA) are obtained by using a keV inn beam. ZnO films are grown on glass substrates by ion beam sputter deposition. changing the oxygen/argon gas ratio, ion beam energy, and substrate temperature. Physical properties of ZnO films were investigated by X-ray diffraction, Rutherford backscattering spectroscopy, and the Van der Pauw method. All the films show a strong preferred orientation along the c-axis. The electrical resistivity is varied from 10(-3) to 10(6) Omega cm and its dependence on the deposition parameters is discussed. The PMMA surface was modified by the ion-assisted reaction technique. Ion dose, ion energy, and oxygen gas now rate are varied from 5 x 10(15) to 1 x 10(17) ions/cm(2), from 0.6 to 1.2 kV, and from 0 to 8 ml/min, respectively. A highly wettable PMMA surface can be obtained by irradiating oxygen ions in an oxygen gas environment. X-ray photoelectron spectroscopic analysis shows that hydrophilic groups are formed on the surface of PMMA.